Antidiabetic activity of selected indigenous Thai medicinal plants - Brantner, Adelheid; Alajlani, M; Autz, C; Benetik, S; Plhak, E; Prinz, Rainer; Pitakbut, Thanet; Dej-Adisai, Sukanya (Planta Medica, 2016)
In Asia, medicinal plants are applied for the treatment of many diseases including diabetes mellitus [1]. In this study Bauhinia malabarica (Roxb.) leaves, Caesalpinia pulcherrima (Linn.) Swartz flowers and leaves and C. coriaria (Jacq.) Willd leaves [Fabaceae] were investigated for their antidiabetic activity. The dried and powdered plant parts were extracted by percolation with solvents of different polarities: n-hexane, ethyl acetate, ethanol and water. The activity of all of the gained extracts at 8 mg/mL was compared to acarbose using an in vitro α-glucosidase inhibitory bioassay. The sample solution and α-glucosidase were mixed with phosphate buffer solution that contained bovine serum albumin and sodium azide. Acarbose 8 mg/ml was used as the positive control, while 5% DMSO was the negative control. The yellow product, p-nitrophenol (pNP) was monitored at 405nm every 30 seconds by micro plate reader. The velocity was determined by the linear relationship equation between absorbance and time [2]. The most significant inhibitory activity was detected from all ethanolic extracts ranging from 89% to 96%, while acarbose resulted in 84% inhibition. The other extracts inhibited the α-glucosidase to a lower extent. This is due to different polarities of the extracted compounds. Further separation of the highly active ethanolic extracts was performed using different chromatographic methods. Isoquercitrin, quercitrin, myricitrin, and luteolin were isolated. The isolated compounds (8 mg/ml) showed α-glucosidase inhibition. Isoquercitrin isolated from B. malabarica and quercitrin from C. pulcherrima leaves showed inhibition of 57% and 71%, respectively. This implies that other ingredients may contribute to the α-glucosidase inhibitory activity. This study confirmed the importance of these investigated medicinal plants for their potential antidiabetic activity <br